Effects of age and height on selected properties of Malaysian bamboo (Gigantochloa levis) - Abdullah Siam, Nordahlia; Uyup, Mohd Khairun Anwar; Husain, Hamdan; Ashaari, Zaidon; Md. Tahir, Paridah; Othman, Abd Razak (Forest Research Institute Malaysia, 2012)
Effects of age and height on the fibre morphology, density, modulus of rupture (MOR) and modulus of elasticity (MOE) of Gigantochloa levis (buluh beting) were studied on 2- and 4-year-old bamboo. There was no significant difference in bamboo properties in relation to age, except that the 4-year-old bamboo had thicker fibre wall. However, culm height affected fibre length and density at both ages. Fibre diameter, fibre wall thickness, MOR and MOE differed significantly with height in 2-year-old bamboo.